Assessment of Inadequate Use of Pediatric Emergency Medical Transport Services: The Pediatric Emergency and Ambulance Critical Evaluation (PEACE) Study - Poryo, Martin; Burger, Martin; Wagenpfeil, Stefan; Ziegler, Bennet; Sauer, Harald; Flotats-Bastardas, Marina; Grundmann, Ulrich; Zemlin, Michael; Meyer, Sascha (Frontiers in Pediatrics, 2019)
Aim: To provide data on the inadequate use of emergency medical transports services (EMTS) in children and underlying risk factors. Methods: This was a prospective single-center cohort study (01/2017-12/2017) performed at the Saarland University Children´s Hospital, Homburg, Germany. Patients ≤20 years of age transported by EMTS for suspected acute illness/trauma were included and proportion of inadequate/adequate EMTS use, underlying contributing factors, and additional costs were analyzed. Results: 379 patients (mean age: 9.0±6.3 years; 55.7% male, 44.3% female) were included in this study. The three most common reasons for EMTS use were: central nervous system (30.6%), respiratory system affection (14.0%), and traumas (13.2%). ETMS use was categorized as inadequate depending on physician´s experience: senior physician (58.8%), pediatrician (54.9%), resident (52.7%). All three physicians considered 127 (33.5 %) cases to be medically indicated for transportation by EMTS, and 177 (46.7 %) to be medically not indicated. The following parameters were significantly associated with inadequate EMTS use: non-acute onset of symptoms (OR 2.5), parental perception as non-life-threatening (OR 1.7), subsequent out-patient treatment (OR 4.0). Conversely, transport by an emergency physician (OR 3.5) and first time parental EMTS-call (OR 1.7) were associated with adequate use of EMTS. Moreover, a significant relation existed between maternal respectively paternal educational status and inadequate EMTS use (each p = 0.01). Using multiple logistic regression analysis, non-acute onset of symptoms (OR 2.2) was associated with inadequate use of EMTS while first time parental EMTS call (OR 1.8), transport by an emergency physician (OR 3.3), and need for in-patient treatment (OR 4.0) were associated with adequate use of EMTS. Conclusion: A substantial number of pediatric EMTS is medically not indicated. Possibly, specific measures including multifaceted educational efforts may be helpful in reducing unnecessary EMTS use.